Adequacy of training in adolescent health: opinions of family physicians and nurses who attended a training course (Portuguese Journal of Family Medicine and General Practice, 2018)
Objectives: To assess the perceptions of primary care professionals on the training received in adolescent health, and to identify the perceived limitations and additional training needs.Study design: Observational, cross-sectional and descriptive study.Setting: Centre region.Population: Family physicians and nurses of the Centre region.Methods: The family physicians and nurses enrolled in an adolescent health training session were invited to answer a survey in which they were asked to evaluate their pre- and post-graduate training in adolescent health, the need to receive further training, and the limitations.Results: Most participants considered that their pre-graduate training was insufficient (physicians: 97%; nurses: 77.2%) and did not feel able to deal with adolescents after graduation (physicians: 93.9%; nurses: 87.7%). The majority of family physicians also considered that the training received during residency was insufficient (77.5%); they didn’t feel able to deal with adolescents upon finishing residency (68.4%), and considered that the training received after residency was also insufficient (73.0%). Participants considered that they need additional training in adolescent health, pointing out areas with greater training needs: psychosomatic complaints (82.2%), family problems (72.9%), clinical interview (69.5%), substance use (62.6%), and school and behavioral problems (62.3%).Conclusions: The family physicians and nurses interviewed reported significant training gaps in adolescent health, both in their pre- and post-graduate training, as well as the need to obtain further training in this area.
Keywords: Education; Adolescent health; Primary health care.